Utilização de agregados de RCC e resíduo de polimento de placas cimentícias em artefatos de concreto - Leviski, Anderson (2016)
Civil Construction is one of the sectors that consumes the rawest materials and also generates municipal solid waste. It is important that less raw materials are consumed and that waste generated is used. One of the proposals for this situation would be to recycle these wastes and turn them into aggregates and filers and then use them in the production of concrete. There are still many barriers to the use of these aggregates and filers in concrete, with and without structural function, and among the main reasons is the difficulty of achieving similar resistance to concrete produced with natural raw materials. Due to this fact, a study was proposed to analyze the influence of the packing of particles in the recycled aggregates and to verify the possibility of using the filter of powder of the polishing of the concrete plates for floor covering. Initially, two batches of recycled aggregates were characterized and only that of concrete residue was considered adequate for the study. Three experimental schedules were proposed, composed of 4 factors of the mixtures, plus the aggregates, filer and Portland cement CP-V. Samples were analyzed for the sample masses, considering the entire grain size range, as well as samples without material passing through the sieve with a 0.150 mm opening. The amount of water was determined by the Vebe consist meter, and from this data, the excess paste was calculated. After the test specimens were obtained, under vibrarocompaction, the behavior of the mechanical resistance and the water absorption were determined. The analysis of the results showed that the best packaging of particles of the aggregates occurs in the range of 42% to 58% of hail. The filer used in large quantities significantly increases the consumption of kneading water and excess paste, and consequently, increased water absorption and loss of strength of dry concrete. However, in smaller amounts than the pore volume, the inclusion of the filer is acceptable, since there is no separation of the particles. It was concluded that in the granulometric range studied, there was no change in mechanical strength, being the preponderant factor the concentration of cement. The observed compressive strengths show that these aggregates can be used in the manufacture of concrete artifacts, such as the production of sealing blocks.